Starlift Like a Phoenix From the Ashes - Noel, Marcia (Express)
The article talks about the history of Starlift and their accomplishments as this year they celebrate their 40th anniversary. Starlift hopes to rise from the ashes and take their place on winner's row. Starlift is an unsponsored band and has resorted to fund-raising ventures throughout the year. For Panorama, a new arranger, Emmanuel Ector, will be arranging Kitchener's "The Power of Music" for the band.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel band music -- Trinidad and Tobago